2016
DOI: 10.1210/en.2015-1603
|View full text |Cite
|
Sign up to set email alerts
|

Trenbolone Improves Cardiometabolic Risk Factors and Myocardial Tolerance to Ischemia-Reperfusion in Male Rats With Testosterone-Deficient Metabolic Syndrome

Abstract: The increasing prevalence of obesity adds another dimension to the pathophysiology of testosterone (TEST) deficiency (TD) and potentially impairs the therapeutic efficacy of classical TEST replacement therapy. We investigated the therapeutic effects of selective androgen receptor modulation with trenbolone (TREN) in a model of TD with the metabolic syndrome (MetS). Male Wistar rats (n=50) were fed either a control standard rat chow (CTRL) or a high-fat/high-sucrose (HF/HS) diet. After 8 weeks of feeding, rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Testosterone (T1500, Merck) was dissolved in 45% 2-Hydroxypropyl-β-cyclodextrin in water 84 to obtain a solution of 22 mg/ml for sustained delivery. This solution or its vehicle was introduced inside Alzet osmotic minipumps (Model 2004, Durect Corporation, Cupertino, CA, USA) to achieve a testosterone delivery of 6 μg/h, based on previous studies obtaining significant effects in orchidectomized mice 29 , 85 .…”
Section: Methodsmentioning
confidence: 99%
“…Testosterone (T1500, Merck) was dissolved in 45% 2-Hydroxypropyl-β-cyclodextrin in water 84 to obtain a solution of 22 mg/ml for sustained delivery. This solution or its vehicle was introduced inside Alzet osmotic minipumps (Model 2004, Durect Corporation, Cupertino, CA, USA) to achieve a testosterone delivery of 6 μg/h, based on previous studies obtaining significant effects in orchidectomized mice 29 , 85 .…”
Section: Methodsmentioning
confidence: 99%
“…17β-Hydroxyestra-4,9,11-trien-3-one (Trenbolone ( 3 ), Figure ), as a synthetic analog of testosterone, is a potent anabolic–androgenic steroid and can be used as a selective androgen receptor modulator in the treatment of obesity and androgen insensitivity syndromes in humans . This special physiological activity has been attributed mainly to the presence of a double bond between carbons 11 and 12, which slows down the metabolism of 3 , greatly increases its binding affinity to the androgen receptor, and inhibits it from aromatizing .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that obese insulin-resistant rats subjected to testos terone deprivation in middle age had an exacerbated insulin-resistant condition as indicated by increased HOMA-IR [12]. In addition, LV mass was also reduced and serum CK-MB levels were increased in testosterone-deprived obese insulin-resistant rats subjected to myocardial ischemia reperfusion injury [13]. Currently, the process involved in the alteration of cardiometabolic function in testosterone-deprived obese insulin-resistant rats remains unknown.…”
Section: Introductionmentioning
confidence: 99%